Circulating Inflammatory and Hemostatic Biomarkers are Associated with All-Cause Death and Cancer Death in a Population of Community-Dwelling Japanese: The Tanushimaru Study - Mika Enomoto; Hisashi Adachi; Ako Fukami; Ayako Yoshimura; Aya Obuchi; Sachiko Nakamura; Yume Nohara; Erika Nakao; Yoko Umeki; Kensuke Hori; Yoshihiro Fukumoto (Clinical Medicine Insights: Cardiology, 2014)
Background In patients with cardiovascular diseases, inflammatory and hemostatic biomarkers are significant indicators of prognosis. We investigated whether circulating inflammatory and hemostatic biomarkers were predictive markers for all-cause death and cancer death in a population of community-dwelling Japanese. Methods We studied 1,920 healthy Japanese adults who underwent health examinations in 1999. Those who reported a history of inflammatory diseases and malignancy on a baseline questionnaire were excluded. Inflammatory and hemostatic biomarkers were measured in the remaining 1,862 participants, who were followed up periodically for 10 years. Multivariate proportional hazards regression analysis was used to estimate all-cause and cancer mortality. Results A total of 258 participants died during follow-up: 87 from cancer, 38 from cerebro-cardiovascular diseases, and 133 from other diseases. Mean C-reactive protein (CRP) levels at baseline were significantly higher in decedents than in survivors. Mean von Willebrand factor (vWF) levels at baseline were significantly higher in decedents than in survivors. The Cox proportional hazards model after adjustments for age and sex showed that CRP (hazard ratio [HR], 1.26; 95% confidence interval [CI], 1.06-1.51) and vWF (HR, 1.01; 95% CI, 1.00-1.01) were independent predictors of all-cause death. CRP (HR, 1.40; 95% CI, 1.06-1.86) and vWF (HR, 1.01; 95% CI, 1.00-1.02) were also independent predictive markers for cancer death. Conclusions Serum CRP and vWF were predictors of all-cause death and cancer death in the population of community dwelling Japanese.